Effects of Spacing and Nitrogen Levels on Growth, Seed Yield and Quality of Spring Okra - T.R. NANDAL; KAMLA KANWAR; RAJENDER SHARMA (Seed Research, 2026)
Field experiment was conducted at CSKHPKV, Hill Agricultural Research and Extension Centre, Dhaulakuan during spring season of 2002 and 2003. It has been observed that none of the spacing treatments showed significant response with respect to plant height, number of branches per plant, fruit length, germination percentage and 100-seed weight. On the other hand, nitrogen levels have shown the increasing trend on growth parameters. Nitrogen @ 100 kg ha recorded significantly higher fruits/plant, seed yield (7.73 q ha), plant height, branches/plant and fruit length. However, germination (%) and 100-seed weight were found to be non-significant with nitrogen at 100 kg ha¹. Spacing of 45 cm x 15 cm was found to be significantly superior to other spacing treatments. It has also recorded the highest fruits/plant and seed yield (6.39 q ha).